Pengaruh Kecerdasan Spiritual dan Hubungan Teman Sebaya terhadap Prestasi Belajar Ekonomi Siswa Kelas X SMA Negeri 2 Lubuk Basung Tahun Ajaran 2018/2019 - Linda Lestari; Elvi Rahmi (Universitas Negeri Padang, 2020)
This study aims to determine the direct influence of spiritual intelligence and peer relationship on economic learning achievement of class X SMAN 2 Lubuk Basung in the 2018/2019 school year. This type of research is quantitative descriptive. The population of this study were all students of class X SMAN 2 Lubuk Basung in the academic year 2018/2019 with a total of 364 students. The sampling technique is proportional random smpling with a sample size of 190 respondents. Data collection techniques are questionnaires and documentation. Data analysis techniques used were descriptive analysis, normality test, heterokedasticity tes, multicollinearity test, multiple regression analysis, F test, and t test. The result of this study indicates that: 1) spiritual intelligence has a positive and significant effect on economic learning achievement, 2) peer relations has a positive and significant effect on economic learning achievement, 3) spiritual intelligence and peer relationship has a significant effect on economic learning achievement. In an effort tp improve economic learning achievement of class X students of SMAN 2 Lubuk Basung Academic Year 2018/2019, student is expected to be able to increase spiritual intelligence and pay attention to peer relationship that have a positive influence to improve learning achievement of economic subjects.Keyword: spiritual intelligence, peer relationship, learning achievement